2018
DOI: 10.4172/neuropsychiatry.1000447
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences within the Psychosis Spectrum

Abstract: Subtle gender differences in cognition arise due to the action of sex hormones during brain development, and are shaped by social influences. The sexes also differ with respect to vulnerability to specific classes of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Nevertheless, some studies have reported that the age of disease onset may vary according to gender, depending on the difference in the common psychiatric diseases in men and women. 28-31 However, when the catatonia group was categorized as “patients with affective disorders” and “patients with psychotic disorder”; there was no difference in the age of onset of the disease in the patients with different disease spectrum, nor in the age of disease onset of men and women in separate disease groups. Conversely, few studies report that the age of disease onset does not differ by gender.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, some studies have reported that the age of disease onset may vary according to gender, depending on the difference in the common psychiatric diseases in men and women. 28-31 However, when the catatonia group was categorized as “patients with affective disorders” and “patients with psychotic disorder”; there was no difference in the age of onset of the disease in the patients with different disease spectrum, nor in the age of disease onset of men and women in separate disease groups. Conversely, few studies report that the age of disease onset does not differ by gender.…”
Section: Discussionmentioning
confidence: 97%